Influence of Winemaking Procedure and Grape Variety on the Colour and Composition of Young Red Wines - González-Neves, G.; Gil, G.; Favre, G.; Baldi, C.; Hernández, N.; Traverso, S. (South African Journal of Enology and Viticulture, 2016)
The influence of winemaking procedure and grape variety on the colour and composition of young red wines was evaluated. For this purpose, Tannat, Syrah and Merlot wines were elaborated in Uruguay in 2011. Traditional maceration (TM), the addition of pectolytic enzymes (ENZ) and cold pre-fermentative maceration before traditional maceration (CPM) were the alternative procedures of winemaking tested. Two batches of grapes (70 kg each) were employed for each winemaking procedure. Tannat wines had the highest colour intensity, red colour (a*), and anthocyanin, proanthocyanidin and alcohol content, and the lowest luminosity (L*) and pH values. CPM increased the colour intensity and total polyphenol, anthocyanin and proanthocyanidin content in Tannat and Merlot wines. Pectolytic additions enhanced colour intensity and red colour and decreased the luminosity in all wines. Meanwhile, enzyme additions enhanced proanthocyanidin content in all cases. Pectolytic enzyme significantly increased the methanol levels of the wines. Nevertheless, the amounts of this compound are far within maximum acceptable limits. Principal component analysis of the data shows significant separation between the wines of each variety, since the colour and composition are largely related to the cultivar and the vintage, despite the effect of the winemaking procedures.